The Problems with Democracy Today - Szahaj, Andrzej (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The text is devoted to the problems of today democracy. Author tries to identify several of them. Very important are those which are connected with lack of liberal component in democracy (phenomenon of so called „unliberal democracy”). But he especially focuses on threat for democracy which is caused by today liberalism (neoliberalism) which inserts the economical dimension of social life above the political one. The main thesis of the text is that this process of depolitization of economical decisions is very dangerous for the democracy because it makes it unimportant and even redundant for the citizens. It shows also that traditional connection of democracy and capitalism is not necessary and can be linked with the short period of Western history only.